Pengaruh Pembelajaran Kooperatif Model Jigsaw terhadap Hasil Belajar IPA Siswa MTs Raudatul Faizin - Isnaini Sapitri Br Purba; Eka Satya; Abdul Fattah Nasution (Jurnal Cakrawala Pendidikan dan Biologi, 2025)
Science learning at the Islamic junior high school level still faces challenges in improving student learning outcomes because the learning process tends to be teacher-centered and lacks active student involvement. This condition requires the implementation of a learning model that can encourage cooperation, responsibility, and student involvement in the learning process. This study aims to determine the effect of the Jigsaw cooperative learning model on the science learning outcomes of students at MTs Raudhatul Faizin. This study uses a quantitative approach with a correlational design. The research subjects consisted of 30 students who were used as the research sample. Data were collected through a four-point Likert scale closed questionnaire to measure the implementation of the Jigsaw cooperative learning model and students' science learning outcomes. Data were analyzed using simple linear regression analysis techniques. The results showed that the Jigsaw cooperative learning model had a significant effect on students' science learning outcomes. This finding indicates that the better the implementation of the Jigsaw cooperative learning model, the better the students' science learning outcomes. The implications of this study emphasize the importance of implementing the Jigsaw cooperative learning model as an alternative effective learning strategy to improve the quality of science learning in Islamic junior high schools.